The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jipb.12779
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide: A novel component in Arabidopsis peroxisomes which triggers catalase inhibition

Abstract: Plant peroxisomes have the capacity to generate different reactive oxygen and nitrogen species (ROS and RNS), such as H 2 O 2 , superoxide radical (O 2 Á À ), nitric oxide and peroxynitrite (ONOO -). These organelles have an active nitrooxidative metabolism which can be exacerbated by adverse stress conditions. Hydrogen sulfide (H 2 S) is a new signaling gasotransmitter which can mediate the posttranslational modification (PTM) persulfidation. We used Arabidopsis thaliana transgenic seedlings expressing cyan f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 79 publications
1
69
2
3
Order By: Relevance
“…These observations are also supported by in vitro biochemical assays in Arabidopsis using H 2 S donors. Thus, it has been shown that H 2 S positively regulates ascorbate peroxidase activity (Aroca et al ) but exerts an inhibitory effect on catalase activity (Corpas et al ). A recent proteomic study of A. thaliana leaves reported that both NADP‐ICDH and NADP‐ME are targets of persulfidation (Aroca et al ) [which is a posttranslational protein modification, similar to protein S ‐nitrosation (Cys‐SNO), mediated by H 2 S that affects thiol groups (Cys‐SSH)].…”
Section: Discussionmentioning
confidence: 99%
“…These observations are also supported by in vitro biochemical assays in Arabidopsis using H 2 S donors. Thus, it has been shown that H 2 S positively regulates ascorbate peroxidase activity (Aroca et al ) but exerts an inhibitory effect on catalase activity (Corpas et al ). A recent proteomic study of A. thaliana leaves reported that both NADP‐ICDH and NADP‐ME are targets of persulfidation (Aroca et al ) [which is a posttranslational protein modification, similar to protein S ‐nitrosation (Cys‐SNO), mediated by H 2 S that affects thiol groups (Cys‐SSH)].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of superoxide dismutase (SOD) activity was confirmed biochemically in various species (reviewed in Corpas et al, 2017), and a Cu-Zn superoxide dismutase (CSD3) was identified in multiple Arabidopsis peroxisome proteomic studies (reviewed in . Peroxisomes also generate RNS under stress conditions such as excess Cd, and probably reactive sulfur species (RSS) as well (Corpas & Barroso, 2014;Corpas et al, 2019a). Proteome analysis showed that numerous peroxisomal proteins are S-nitrosylated or nitrated, implying that RNS has a role in peroxisomal function (Sandalio & Romero-Puertas, 2015).…”
Section: Ros and Rns Metabolismmentioning
confidence: 99%
“…All these data point out the complexity of plant peroxisomal metabolism which seems to be much more intricate than expected, as well as new functions for peroxisomes in the connection with different subcellular compartments. In this sense, very recent data obtained in our laboratory indicated that plant peroxisomes also contain the gasotransmitter hydrogen sulfide (H 2 S) which is a catalase inhibitor (Corpas et al ), and raised new questions on the potential physiological function of H 2 S in the metabolism of plant peroxisomes.…”
Section: Perspectivesmentioning
confidence: 99%